2018
DOI: 10.1155/2018/2525670
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of a Short Period of Supplementation with Glutamine Dipeptide on the Cognitive Responses after a Resistance Training Session of Women with HIV/AIDS: A Randomized Double-Blind Placebo-Controlled Crossover Study

Abstract: The aim of the present study was to investigate the effect of a short period of supplementation with glutamine dipeptide (GDP) on the acute responses to resistance training on the executive functions of people with HIV/AIDS. The sample consisted of 10 HIV+ women (45.00 ± 12.77 years old; 65.71 ± 12.04 kg; 1.54 ± 0.05 m) who were submitted to a randomized double-blind crossover procedure according to two experimental conditions: orally supplemented with 20 g/day of GDP or with maltodextrin for seven days. On th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
0
7
0
Order By: Relevance
“…Other studies also suggest that acute resistance exercise, in people living with or without HIV, is associated with cognitive improvements, especially in executive functions. 24,25,34 Nevertheless, this is the first study to evaluate the isolated acute effect of resistance exercise on cognition among PLHIV. In our study, changes were similar in the CG and the EG after the exercise session.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Other studies also suggest that acute resistance exercise, in people living with or without HIV, is associated with cognitive improvements, especially in executive functions. 24,25,34 Nevertheless, this is the first study to evaluate the isolated acute effect of resistance exercise on cognition among PLHIV. In our study, changes were similar in the CG and the EG after the exercise session.…”
Section: Discussionmentioning
confidence: 99%
“…Souza et al. 25 is the only study published to date, which demonstrated the acute impact of RE on the attention and inhibition of women living with HIV . However, this study has two peculiarities when compared to the present research.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies have demonstrated the relation between glutamine and anti-inflammatory effects by showing their influence on inflammatory signaling pathways, including the nuclear factor κB (NF-κB) and signal transducer and activator of transcription (STAT) [13]. Other studies show that glutamine can modulate aspects of the central nervous system and improve psychobiological aspects [12,14,15]. For example, glutamine supplementation can reduce subjective fatigue and ratings of perceived exertion during demanding tasks [13,16].…”
Section: Introductionmentioning
confidence: 99%